2004
DOI: 10.1111/j.0022-202x.2004.23436.x
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Hair Loss and Myocardial Degeneration in Rough Coat Mice: Reduced Lysyl Oxidase-Like (LOXL) in the Skin and Heart

Abstract: The rough coat (rc) is a spontaneous recessive mutation in mice. To identify the mutated gene, we have characterized the rc phenotype and initiated linkage mapping. The rc mice show growth retardation, cyclic and progressive hair loss, hyperplastic epidermis, abnormal hair follicles, cardiac muscle degeneration, and reduced amount of collagen and elastin in the skin and heart. The rc locus was mapped at 32.0 cM on chromosome 9, close to the loxl gene. Lysyl oxidase-like (LOXL) protein is a novel copper-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 33 publications
(39 reference statements)
3
27
0
Order By: Relevance
“…However, full alopecia was reported in Mpzl3 rc mice greater than 1 yr of age (7,21). Several other phenotypic changes were noted in Mpzl3 rc mice, including elevated blood calcium levels and myocardial fiber degeneration (21). Our studies failed to find these differences 14 C]acetate, and lipids were extracted with a 2:1 mixture of chloroform-methanol.…”
Section: E289mentioning
confidence: 60%
See 2 more Smart Citations
“…However, full alopecia was reported in Mpzl3 rc mice greater than 1 yr of age (7,21). Several other phenotypic changes were noted in Mpzl3 rc mice, including elevated blood calcium levels and myocardial fiber degeneration (21). Our studies failed to find these differences 14 C]acetate, and lipids were extracted with a 2:1 mixture of chloroform-methanol.…”
Section: E289mentioning
confidence: 60%
“…Furthermore, none of the mice we examined between 1 and 2 yr of age had complete fur loss; nor were significant differences in the extent of fur loss noted between KO mice that were 1-2 yr old. However, full alopecia was reported in Mpzl3 rc mice greater than 1 yr of age (7,21). Several other phenotypic changes were noted in Mpzl3 rc mice, including elevated blood calcium levels and myocardial fiber degeneration (21).…”
Section: E289mentioning
confidence: 99%
See 1 more Smart Citation
“…These are known as LOX, LOXL, LOXL2, LOXL3, and LOXL4 in humans (Kagan et al, 1995). Each LOX family protein contains a copper-binding motif, lysyl-tyrosyl-quinone (LTQ) residues, and a cytokine receptor-like (CRL) domain in its highly conserved carboxyl (C)-terminus (Hayashi et al, 2004a). The main molecular function of the LOX enzyme is lysyl oxidation to make protein cross-linking through lysine residues.…”
Section: Introductionmentioning
confidence: 99%
“…5 A recent study indicated that the downregulation of LOX-L1 in skin and heart of mice may produce the rough coat (rc) phenotype from a spontaneous mutation. 20 However, the oncogenic potential of LOX-L1 was rarely Figure 3 The distribution of normalized mRNA expression level of LOXL genes in tissue pairs. The statistical analysis is summarized in Table 3.…”
Section: Discussionmentioning
confidence: 99%